Characterization of Porcine Ventral Mesencephalic Precursor Cells following Long-Term Propagation in 3D Culture - Pia S. Jensen; Lise Lyck; Pia Jensen; Jens Zimmer; Morten Meyer (Stem Cells International)
The potential use of predifferentiated neural precursor cells for treatment of a neurological disorder like Parkinson’s disease combines stem cell research with previous experimental and clinical transplantation of developing dopaminergic neurons. One current obstacle is, however, the lack of ability to generate dopaminergic neurons after long-term in vitro propagation of the cells. The domestic pig is considered a useful nonprimate large animal model in neuroscience, because of a better resemblance of the larger gyrencephalic pig brain to the human brain than the commonly used brains of smaller rodents. In the present study, porcine embryonic (28–30 days), ventral mesencephalic precursor cells were isolated and propagated as free-floating neural tissue spheres in medium containing epidermal growth factor and fibroblast growth factor 2. For passaging, the tissue spheres were cut into quarters, avoiding mechanical or enzymatic dissociation in order to minimize cellular trauma and preserve intercellular contacts. Spheres were propagated for up to 237 days with analysis of cellular content and differentiation at various time points. Our study provides the first demonstration that porcine ventral mesencephalic precursor cells can be long-term propagated as neural tissue spheres, thereby providing an experimental 3D in vitro model for studies of neural precursor cells, their niche, and differentiation capacity.